Thermal bonding and surface modification in the fabrication of COC polymer based microfluidic devices - Roy, Sunanda (2014)
Cyclic olefin copolymers (COC) are commonly used in the fabrication of microfluidic devices. Several issues need to be addressed before this can be realized. A fundamental understanding of the factors that affect thermal bond strength between different polymer substrates is necessary.This will enable the selection of suitable substrate pairs so that good thermal sealing between two polymeric substrates in microfluidic devices can be obtained. Furthermore, the intrinsically hydrophobic character of the COC surface has to be rendered hydrophilic to facilitate flow and electrophoretic separation.